Molecular Detection for Japanese Encephalitis and Chikungunya Virus as Etiology Agent for Dengue-Like Fever Symptoms - Ariani, Rizka; Sudiro, Tjahjani M; Dewi, Beti E (UI Scholars Hub, 2018)
Background: Acute fever with dengue-like fever symptoms with headache, rash, arthritis, perifer bleeding like ptechie and rinhorrhea are symptoms that often complained by patient and it may be caused by arboviruses infection. Arboviruses are very endemic in Indonesia, especially Dengue Virus (DENV), Japanese Encephalisitis Virus (JEV), and Chikungunya Virus (CHIKV) that causing similar symptoms. Molecular detection is very important to confirm the etiology for adequate management. Methods: This study investigated the etiological agent using one step real time RT reverse transcription polymerase chain reaction (RT PCR) method and SYBR Green I as fluorescent binding dye reporter. The viruses that were investigated were JEV and CHIKV. Primer design was using online software NCBI. Those primers fulfill the good primer requirements and can be used as material in RT PCR reaction. Results: The optimum temperature for all primers were at 60 °C. The limit detection of JEV primer was 4355 copy DNA every reaction. Cross reactivity between all primers with DENV serotype 2 RNA and false positive result using healthy person sample were not found. Conclusions: This study has optimized condition RT PCR protocol that can be used as diagnostic tools for patient with dengue-like fever symptoms.